Globalization - challenges and opportunities for transition economies - Grzegorz W. Kołodko (Transformation, Integration and Globalization Economic Research (TIGER), 2003)
Globalization is a vague concept, used for some time, whose various stages can be traced to the XV century. From the economic perspective it is the historical process of gradual liberalization followed by progressive integration of fragmented capital and commodity markets, the markets of services, and, to a lesser extent and somewhat belatedly, also labor markets, into a single world market. It has number of dimensions such as cultural, technological and, as mentioned above, economic ones. Globalization has tremendous effects on the countries in systemic transition, populated by 1,7 billion people. The process of globalization brings opportunities but also threats and risks, benefits, but also costs. It serves as a catalyst of post-socialist transformation, but at the same time can lead to marginalization, as the fruits of globalization are not given automatically and very much depend on the geo-political position and states' policies.
Keywords: 330; Globalisierung; Systemtransformation; Polen; Transformationsstaaten